A methodology for greenhouse gas emission and carbon sequestration assessments in agriculture: Supplemental materials for info series analyzing low emissions agricultural practices in USAID development projects - Grewer, Uwe; Bockel, Louis; Galford, Gillian L.; Gurwick, Noel; Nash, Julie; Pirolli, Gillian; Wollenberg, Eva Karoline (2016)
As many countries are increasing commitments to address climate change, national governments are exploring how they could best reduce the impact of their greenhouse gas (GHG) emissions. Agriculture is a major contributor to GHG emissions, especially in developing countries, where this sector accounts for an average of 35% of all GHG emissions. Yet many agricultural interventions can also help to reduce GHG impacts. This paper presents the methodology to estimate impacts of agricultural interventions on GHG emissions and carbon sequestration. This methodology is used in an analysis of several development projects supported by the United States Agency for International Development (USAID) and presented as a series of case studies. The methodology allows users to estimate (1) GHG impacts at project scale, (2) GHG emissions by agricultural practice, and (3) GHG emissions per unit of output (i.e., GHG emission intensity). The presented approach is a rapid assessment technique that is well suited to provide an indication of the magnitude of GHG impacts and to compare GHG impact strength of different field activities or cropping systems. It is well adapted to a context of data scarcity, as is common in agricultural investment planning where aggregate data on agricultural land use and management practices are available but where field measurements of GHG and carbon stock changes are missing. This approach is instrumental to inform agricultural investment, project, and policy planners about challenges and opportunities associated with achieving and accounting for GHG emission reductions in agricultural development projects.